A META-ANALYSIS OF RESEARCH ON THE MEDIATED EFFECTS OF PRINCIPAL LEADERSHIP ON STUDENT ACHIEVEMENT : EXAMINING THE EFFECT SIZE OF SCHOOL CULTURE ON STUDENT ACHIEVEMENT AS AN INDICATOR OF TEACHER EFFECTIVENESS - Bulris, Mark Ellsworth (East Carolina University, 2009)
The leadership of the school principal has long been associated with teacher effectiveness and student achievement. Research on the topic of principal leadership supports this association (Hallinger, Bickman, & Davis, 1996; Hallinger & Heck, 1996, 1997; Leithwood, Louis, Anderson, & Wahlstrom, 2004; Walters, Marzano, & McNulty, 2003). Research indicates that this association is indirect and occurs through mediating factors (Hallinger et al., 1996; Hallinger & Heck, 1996, 1997; Leithwood, Louis et al., 2004; Robinson, 2007). These factors include intervening variables such as a school's vision and mission, teacher's pedagogical and content knowledge, teacher instructional practices, and school culture. A review of the literature on mediating variables reveals school culture as a mediating variable that may have a significant relationship with improved teacher effectiveness.   Schoen and Teddlie's (2008) model of school culture was selected as the operational definition of school culture for the present study. The review of literature leads to multiple models of teacher effectiveness and provides justification for using student achievement as a proxy measure of teacher   effectiveness. Using Schoen and Teddlie's model of school culture and student achievement as a proxy measure for teacher effectiveness, the study uses   meta-analysis techniques to examine the effect size of school culture on student achievement in K-12 schools in the United States.  The study synthesizes correlational study findings between school culture and student achievement since the signing of Goals 2000 in 1994. Studies included in the meta-analysis were conducted in U.S. public schools and included correlations in the form of a Pearson r between one or more of the dimensions of school culture and student achievement. The review of literature produced 30 studies meeting all established criteria for inclusion, provided a total of 152 correlations, and included 3,378 schools. The results of the study indicate that a strong moderate effect exists between school culture and student achievement in K-12 schools in the United States. The results indicate that school culture is a significant mediating variable of principal leadership and student achievement.
Keywords: Education, General; Principal leadership; School culture; Teacher effectiveness; School principals--United States; Teacher effectiveness--United States; Academic achievement--United States; Teacher-principal relationships--United States; Teacher-student relationships--United States; Interaction analysis in education; Educational leadership--United States